(untitled) (Bangladesh Agronomy Journal, 2022)
Farmers’ existing rice production practices provide key indications of interventions for improving yield in their environments. This study aimed to explore those indications in the Fallow - T. Aman rice - Fallow cropping pattern (CP) under rainfed farming practiced by the farmers in Kapasia, Gazipur. Research method employed one-to-one and face-to face interview of 154 farmers practicing the CP. The average yield of T. Aman was estimated as 3.23 t ha-1, slightly below the national average yield of 3.93 t ha-1, in the range of 1.18 to 5.65 t ha-1. Variety was one of the two broad factors that determined the yield variation. The high yeld potential (HYP) category absolutely preferred the production aim, where Swarna-Ranjit (31.2% by farmer) and BRRI dhan49 (24.7% by farmer) were the dominated varieties where average yields were very close (3.51 and 3.36 t ha-1) for Swarna-Ranjit and BRRI dhan49, respectively). Management was the second factor determining the yield variation within varieties. While both the varieties received similar maximum yield (5.65 t ha-1), Swarna-Ranjit produced the minimum yield of 1.40 t ha-1 and BRRI dhan49 of 1.98 t ha-1. This study did not find a consistent pattern of response of the three measured management components - transplanting time, seedling age and seedling density to yield in either variety. The yield variance of BRRI dhan49 under three management components was higher compared to Swarna-Ranjit. Farmers practiced relatively a wide range of three management combinations to achieve high yield in Swarna-Ranjit, but a narrow range of the three management combinations for BRRI dhan49 to achieve the same level of yield. It is concluded that the variety-specific agronomic management to be the avenue for yield improvements in farmers’ fields. Bangladesh Agron. J. 2022, 25(1): 23-36